PENGEMBANGAN SISTEM INFORMASI GEOGRAFIS (SIG) PENYEDIA LAYANAN KESEHATAN BERBASIS ANDROID - Budiman Ruliansyah; Kurnia Muludi; Febi Eka Febriansyah (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2016)
Geographic Information Systems (GIS) is an information system which is used to input, process and generate geographically or geospatial referenced data to support the decision making in a planning. This technology can be used on an Android-based smartphone. Internet, accelerometer, digital maps and GPS (Global Positioning System) on Android can be integrated so that GIS can be implemented. In this study, GIS technology is implemented to detect and find the location of health care providers in city of Bandar Lampung. This application is designed and implemented by using Java programming language and Google Maps API to show the location of health care providers. Testing phase by using Equivalence Partitioning method indicates that the function of the application has been running in accordance with the analysis.Â Keywords : Android, Application, Geographic Information System, Healthcare Provider, Map.